Baicalein prevents 6-OHDA/ascorbic acid-induced calcium-dependent dopaminergic neuronal cell death - Sheng-Fang Wang (Scientific Reports, 2017)
Abstract 6-OHDA plus ascorbic acid (AA) has long been used to induce Parkinson’s disease in rodents, while only 6-OHDA is commonly used to induce cell damage in cellular PD models. AA was believed to act as an anti-oxidant to prevent the degradation of 6-OHDA; however, some studies suggested that AA dramatically enhanced the selectivity and toxicity of 6-OHDA. To understand the mechanisms by which 6-OHDA/AA induces cell death, we established a 6-OHDA/AA cell toxicity model in human dopaminergic neuroblastoma SH-SY5Y cells. We confirmed that the toxicity of 6-OHDA was dramatically increased in the presence of AA, and the toxicity can be prevented by a flavonoid, baicalein. Mechanistically, our research reveals that 6-OHDA/AA induces cell death mainly through the interruption of intracellular calcium homeostasis, which leads to calpain activation and mitochondrial damage. Baicalein prevents 6-OHDA/AA-induced intracellular calcium elevation as well as consequent mitochondria damage. Taken together, our study confirms that 6-OHDA/AA is a more sensitive model for inducing neuronal lesion in vitro and reveals the central role of intracellular calcium in 6-OHDA/AA-induced cell death. Our studies further show that baicalein prevents 6-OHDA/AA-induced cell death by inhibiting intracellular calcium elevation.